2017
DOI: 10.1093/jisesa/iex064
|View full text |Cite
|
Sign up to set email alerts
|

OUP accepted manuscript

Abstract: As an important economic insect, silkworm Bombyx mori (L.) (Lepidoptera: Bombycidae) has numerous advantages in life science, such as low breeding cost, large progeny size, short generation time, and clear genetic background. Additionally, there are rich genetic resources associated with silkworms. The completion of the silkworm genome has further accelerated it to be a modern model organism in life science. Genomic studies showed that some silkworm genes are highly homologous to certain genes related to human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 57 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Corresponding to the phylogenetic analysis performed with the mcmctree program of the PAML package 19 (parameters: rootage, 1,000; clock, 3; alpha, 0.603820) ( Yang, 1997 ), Figure 3A shows that Bmj has a very close relationship to Bmo and phylogenetically diverged from the common ancestor ∼3 million years ago. However, the history of human breeding is up to 5,000 years long ( Tabunoki et al, 2016 ; Meng et al, 2017 ), and the best explanation is manual intervention in sericulture, which increases their divergence. By using the phylogenetic analysis as a supplement, the above-mentioned 650 single-copy gene families were subjected to internal alignment with MUSCLE, 20 and then the aligned results were merged to form a super alignment matrix ( Edgar, 2004a , b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corresponding to the phylogenetic analysis performed with the mcmctree program of the PAML package 19 (parameters: rootage, 1,000; clock, 3; alpha, 0.603820) ( Yang, 1997 ), Figure 3A shows that Bmj has a very close relationship to Bmo and phylogenetically diverged from the common ancestor ∼3 million years ago. However, the history of human breeding is up to 5,000 years long ( Tabunoki et al, 2016 ; Meng et al, 2017 ), and the best explanation is manual intervention in sericulture, which increases their divergence. By using the phylogenetic analysis as a supplement, the above-mentioned 650 single-copy gene families were subjected to internal alignment with MUSCLE, 20 and then the aligned results were merged to form a super alignment matrix ( Edgar, 2004a , b ).…”
Section: Resultsmentioning
confidence: 99%
“…With advances of biotechnology, B. mori has been treated as an important bioreactor for producing recombinant protein ( Tomita et al, 2000 , 2003 ). Moreover, because of their intermediate genome size, short life cycle, affordability, and ability to be easily used for drug screening, B. mori is a perfect model organism for scientific discovery, especially for lepidopterans, and is useful for economic research ( Kaito et al, 2002 ; International Silkworm Genome, 2008 ; Tabunoki et al, 2016 ; Meng et al, 2017 ). To maintain the consistency of biological background among different laboratories, the B. mori strains of Dazao and p50T were first separately sequenced and annotated in China and Japan by whole-genome shotgun sequencing in 2004, and the genome sequence has been updated every few years, which is considered the gold standard ( Mita et al, 2004 ; Xia et al, 2004 ; Meng et al, 2017 ; Kawamoto et al, 2019 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Experiments using the silkworm evaluation system revealed that the viscous component of natto has a suppressive effect against sucrose-and glucose-induced hyperglycemia. Silkworms are useful for large-scale in vivo evaluation because they are inexpensive and can be reared in large groups (21)(22)(23)(24)(25)(26)(27). We reported the discovery of several active substances that suppress postprandial hyperglycemia using the silkworm evaluation system (4,11,28).…”
Section: Discussionmentioning
confidence: 99%
“…Bombyx mori is an economically important invertebrate and a research model for Lepidoptera insects. 15 Genome-editing tools, including ZFN, TALEN, CRISPR-Cas9, BE3, and genomewide CRISPR screening, have been applied in B. mori. [16][17][18][19][20][21][22][23] Increasing studies and applications of genome editing technologies in B. mori are being performed and have greatly accelerated the silkworm biology and sericulture industry.…”
Section: Introductionmentioning
confidence: 99%